Evaluation of Carbon-Based Interconnects for Digital Signaling in Printed Flexible Electronics on Sustainable Substrates - Wang, Zixin; Saleh, Mahdi; Alwattar, Aula; Alfredsson, Maria; Horne, Robert J.; Ang, Chee S.; Condell, Joan; Flowers, Emily; Matcham, Faith; Robinson, Tony; Rooksby, John; Saha, Sian; et al. (IEEE journal on flexible electronics, 2025)
Printed electronics using flexible substrates are an emerging area, allowing next-generation electronics to conform and flex with different surfaces, from human skin to clothing. In the hybrid integration or sea-of-rigids, approach, conventional microchips are mounted onto (generally) plastic substrates such as polyethylene naphthalate (PEN), with (typically) printed silver tracks for interconnections between components. An ongoing research direction is to replace plastic substrates with biodegradable substrates and to replace silver tracks with nonheavy metal-based tracks. While the substrates and tracks form only part of an overall system, replacing them is a step toward increased sustainability and helps to meet net-zero goals for printed electronic systems. Previously, several papers have investigated printed carbon tracks for low-frequency analog sensing applications. This article explores the feasibility of using printed carbon tracks on biodegradable substrates for high-frequency applications such as digital signaling over a serial-peripheral interface (SPI). We investigate the printability, thermal stability, and electrical conductivity of carbon ink screen-printed onto six commercially available sustainable and flexible substrates. Our results demonstrate that multilayer screen printing substantially reduced the electrical resistance of carbon tracks, enabling SPI communication at frequencies up to 16 MHz with three layers of carbon ink. A Natureflex substrate provided the best balance of printability, thermal stability, and electrical performance. Substrates such as greaseproof paper and ClearFilm PU showed potential for flexible electronics, but require further optimization. This study provides valuable insights into selecting and optimizing biodegradable substrates for high-frequency digital systems, supporting the move toward more sustainable printed electronics.